ANALISIS TINGKAT DAN POLA SEBARAN KEBISINGAN AKIBAT AKTIVITAS PEMBANGUNAN GEDUNG REKTORAT PADA LINGKUNGAN KAMPUS II UNIVERSITAS MUHAMMADIYAH RIAU - Delovita Ginting; Noni Febriani; - Rusmi (LPPM Universitas Muhammadiyah Riau, 2016)
This study analyzes the distribution of noise levels and noise mapping patterns at Campus II the University of Muhammadiyah Riau. One of the factors that affect the learning process is concentration, concentration problems may occur due to the disruption of air pollution around is noise. One of the biggest contributors to the noise is a building process on campus. Noise level measurements performed at 6 points using sound meters. Measurements were performed for 10 minutes on each point. Distribution noise mapping pattern levels using a surfer 11. The results show has a maximum noise level is 80.9 dB. Results of mapping the intensity of noise during the day showed the highest noise levels at the west, while at night showed the highest noise levels in southern locations.